Left Main Percutaneous Coronary Intervention and Transcatheter Aortic Valve Replacement in a Young Male with Rheumatic Heart Disease and Porcelain Aorta. (22nd June 2016) - Chainani, Vinod; Perez, Osman; Hanno, Ram; Hourani, Patrick; Rengifo-Moreno, Pablo; Martinez-Clark, Pedro; Alfonso, Carlos E.
Abstract : We highlight the presence of a calcified mass in the left main coronary artery without significant atherosclerosis seen in the other coronary arteries or in the peripheral large arteries. In our view, the calcified character of the obstruction and the calcification of the aortic valve are characteristic of a variant type of coronary artery disease (CAD) not associated with the same risk factors as diffuse coronary atherosclerosis, but, in this case, with rheumatic heart disease. This case report also emphasizes the interventional approach for patients with aortic valve stenosis secondary to rheumatic heart disease.